Serous BMP8A has Clinical Significance in the Ultrasonic Diagnosis of Thyroid Cancer and Promotes Thyroid Cancer Cell Progression - Liu, Kun; Gao, Min; Qin, Dongdong; Wang, Hongjun; Lu, Qixiu (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Objective: This study aims to discover a potential cytokine biomarker for early diagnosis of thyroid cancer. Methods: We employed data mining of The Cancer Genome Atlas (TCGA) and experimentally elucidated its mechanistic contributions. The differential expression genes (DEGs) between thyroid cancer and health population were analyzed with TCGA online bioinformatic tools. The relative expression of Bone Morphogenetic Protein 8A (BMP8A) was determined by real-time PCR in ultrasonic diagnosed thyroid cancer both in vivo and in vitro. The serous BMP8A content was quantified with an ELISA kit. Protein levels of BMP8A, OCLN, ZEB1, EZH2 and β-Actin were analyzed by Western blot. Cell viability was measured by the MTT assay, and anchorage-independent growth was measured by the soft agar colony formation assay. Cell migrative and invasive capacities were interrogated with transwell chamber assays. Results: We identified aberrantly high expression of BMP8A in thyroid cancer, which was associated with unfavorable prognosis and tumor progression. The serous BMP8A was also significantly up-regulated in thyroid cancer patients. Ectopic over-expression of BMP8A remarkably stimulated cell viability and anchorage-independent growth. Meanwhile, the migrative and invasive capacities were greatly increased in response to BMP8A over-expression. Mechanistically, we characterized the positive correlation between BMP8A and TCF7L1, and forced expression of TCF7L1 induced BMP8A expression in TPC-1 cells. Conclusion: In summary, we have identified a novel biomarker for early diagnosis in addition to Ultrasound for thyroid cancer, which is subjected to TCF7L1 regulation.
Keywords: Thyroid cancer